Brincar de letras: literacia emergente e estratégias lúdicas para o desenvolvimento de precursores da alfabetização em crianças pequenas - Garcia-Schmitt, Denise Tosin (2023)
SAEB (Basic Education Assessment System) is a set of large-scale assessments, applied every two years in Brazil, that allows INEP (National Institute of Educational Studies and Research) to carry out a diagnosis of Basic Education and the factors that can interfere with student performance. Due to the adverse scenery in Education during the Covid19 pandemic, results from the year 2019 are currently used to assess the performance of 2nd grade students in Elementary School, on issues related to literacy. Before the pandemic, the results prove that 15% of students, aged around 8, registered in schools in Brazil, were unable to write words alphabetically. Therefore, this research believes it is necessary to review reading and writing skills in the years prior to literacy. To this, we searched the literature for studies and evidences on Emerging Literacy in preschool children (3 to 5 years old) and the contributions to the development of fundamental precursors for reading and writing. Initial and final assessment instruments were applied, with a 14 weeks interval, to 6 children aged between 3 and 5 years. Of the total number of participants, 3 children participated to the intervention with activities from CEL – Set of Playful Strategies, developed for this research, and the other 3 children were not exposed to any type of intervention, in the same period of time. This is an exploratory study with controlled intervention and comparative results, with the aim of observing and reporting whether and how young children evolve when they come into contact with structured activities for the development of: phonological awareness, alphabetic knowledge and vocabulary. The research is based on the Cognitive Science of Reading and phonic teaching and learning instruction. The results indicated significant progress in children participating in the intervention, corroborating other research that highlights the importance of developing literacy skills in young children, to facilitate the path of learning to read and write, decreasing possible difficulties in literacy